An Act To Prohibit the Manufacture, Distribution, Storage, Use, and Possession in Time of War of Explosives, Proving Regulations for the Safe Manufacture, Distribution, Storage, Use, and Possession of the Same, and for Other Purposes, 40 Stat. 385 (1917) - (:unkn) unknown (My University, 1917)
Ch. 83: During war, prohibited the manufacture, distribution, storage, use, possession of powder, explosives, blasting supplies, or ingredients thereof in such a manner detrimental to the public safety.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER